Zoonotic infection by Cryptosporidium fayeri IVgA10G1T1R1 in a Western Australian human. (17th January 2021) - Braima, Kamil; Zahedi, Alireza; Oskam, Charlotte; Austen, Jill; Egan, Siobhon; Reid, Simon; Ryan, Una
Abstract: In the present study, a 37‐year‐old immunosuppressed female in Western Australia (WA) was identified as positive for Cryptosporidium by microscopy and treated with nitazoxanide. Molecular analyses at the 18S ribosomal RNA (18S) and 60 kDa glycoprotein ( gp60 ) loci identified C . fayeri subtype IVgA10G1T1R1, which had previously been identified in western grey kangaroos ( Macropus fuliginosus ) in WA. Next generation sequencing (NGS) of the gp60 locus confirmed the absence of mixed infections with other Cryptosporidium species. This is only the second report of C . fayeri in a human host highlighting the zoonotic potential of this wildlife‐associated species. Routine diagnosis using molecular methods in laboratories is required to better understand the diversity and epidemiology of Cryptosporidium parasite.